Enhancing Arabic Proficiency through Targeted Instructional Programs - Dr K M A AHAMED ZUBAIR (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
This study investigates two interconnected approaches to improving Arabic language proficiency among undergraduate students. The first component analyzes the implementation of a public speaking and oratory program designed to enhance speaking skills (Ade Adin Sahrudin et al.). The second component evaluates the suitability of a standard Balaghah (Arabic rhetoric) textbook based on established pedagogical criteria (Ikhwanul Habib et al.). The research was conducted within the Department of Arabic at The New College, Chennai, India, an institution under the aegis of MEASI. A cohort of 30 undergraduate students, divided into two groups, participated in the integrated instructional program. Qualitative case study methodology, incorporating interviews, observations, and tests, was employed to assess the speaking program (Ade Adin Sahrudin et al.), while descriptive qualitative content analysis was used to evaluate the textbook (Ikhwanul Habib et al.). Findings indicate that focused oratory training significantly improves linguistic aspects (pronunciation, vocabulary) and presentation skills (voice control, intonation, facial expressions, body language), though grammatical accuracy and speech structuring require further attention (Ade Adin Sahrudin et al.). Concurrently, the Balaghah textbook was found to be largely suitable in terms of content, organization, presentation, and alignment with learning objectives, despite minor issues with irrelevant illustrations (Ikhwanul Habib et al.). The study concludes that a dual strategy combining active, skill-based oratory practice with a well-structured theoretical foundation in Balaghah is effective for comprehensive Arabic language development.